ANALISIS KOMPARATIF PERBEDAAN TINGKAT RELIGIUSITAS SISWA DI LEMBAGA PENDIDIKAN PESANTREN, MAN, DAN SMUN - Wahyuni Ismail (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2009)
This study aims at comparing religious application level between students learning at Islamic boarding school, Islamic senior high school, and state senior high school. This study, also, analyzes religious application level in terms of gender, and the domi-nant religious aspect of application. The religious scale was employed to collect data to 225 year-two senior high school students, 110 females and 115 males. The data were analyzed by using a two-way variant. The result indicates that there is a significant difference (p=0,008) in terms of religious application level, where the students of Islamic boarding school are better than those of Islamic senior high school, while the students of Islamic senior high school are better than those of the state senior high school. This study also reveals that female students are better than their male counterparts in terms of religious application (p=0,000). Finally, the study suggests that the religious aspect which students implement dominantly is worship.